Presença de Aloanticorpos Eritrocitários em gestantes Rh negativo, atendidas na Fundação de Hematologia e Hemoterapia do Amazonas (Hemoam). - (:unkn) unknown (Universidade Federal do Amazonas, 2005)
The presence of G class irregular erythrocyte alloantibodies in the blood circulation during pregnancy may cause a series of consequences to the newborn. The alloimmunization can occur under different situations, such as: blood incompatibility during delivery, miscarriage, amniocentese, blood transfusion, among others, all considered being risky. This study investigated the occurrence of regular and irregular circulating alloantibodies in women under the care of the Program of RhD-negative Expecting Mothers (PGRhN) of the Amazonas Hematology and Hemotherapy Foundation (HEMOAM). A retrospective study was carried out compiling the data of all expecting mothers under care during 2003, as well as the information regarding their newborns. A second study, prospective, was done by analyzing the blood samples of expecting mothers under the care of the PGRhN between April and November 2004, as well as the information on their respective babies. All tests were carried out following the methodology presented in the American Association of Blood Bank Technical Manual (2005). The comparison of the alloimmunization frequency between the first (5.6%) and the second (3.5%) studies showed no significant difference. The frequency of antibodies attached to the erythrocytes in the newborns of alloimmunized mothers were high, 67% in the retrospective study and 72.7% in the prospective study. The frequency of G class regular alloantibodies was 87% in the prospective study and the ABO maternal-fetal incompatibility was 17% in O type mothers with A or B type progeny. The occurrence of irregular alloimmunization in the PGRhN is still high, comparing with the numbers of other authors, indicating that the Program may be failing in preventing the problem to occur or errors may have been made during the sorotherapy of patients under risk. Also, it was observed a high frequency of G class regular alloantibodies which can cause the Hemolytic Disease of the Newborn (HDN) due to ABO incompatibility.
Keywords: Aloimunizacao; Aloanticorpos, gestante, Rh negativo; Doença hemolítica do recém-nascido; Alloimmunization; Alloantibodies; Pregnant; RhD-negative; Hemolytic Disease of the Newborn (HDN).; CIÊNCIAS BIOLÓGICAS